Endometriosis pada Luka Operasi Seksio Sesarea: Suatu Laporan Kasus - Yastani, Deasyka; Wirawan, Jimmy Panji; Anastasya, Karina Shasri; Faradilla, Meutia Atika; Xavierees, Endrico; Yohana, Yohana; Suweino, Suweino; Rahmansyah, Mulia; Mahardieni, Karlina; Ferina, Mutiara (Jurnal Biomedika dan Kesehatan, 2025)
Caesarean scar endometriosis is a rare form of extra pelvic extrapelvic or extra-pelvic endometriosis that often presents with nonspecific symptoms, leading to diagnostic challenges. We report the case of a 41-year-old woman who presented with a painful subcutaneous mass at the site of a previous caesarean section, noted eight months post-surgery. MRI imaging revealed a mass suggestive of cutaneous endometriosis, and a wide excision was performed. Histopathological analysis confirmed the diagnosis by identifying endometrial glands and stroma within the cutaneous tissue. We report the case of a 41-year-old woman with a painful subcutaneous mass at the site of a previous cesarean section. The mass was detected eight months after the cesarean section. Following magnetic resonance imaging (MRI), which demonstrated a mass characterized as cutaneous endometriosis, the patient underwent wide excision. Histopathological analysis confirmed the diagnosis by demonstrating endometrial glands and stroma within the cutaneous tissue. Caesarean scar endometriosis is often associated with Pfannenstiel incisions, with a latency period of symptom onset averaging over two years. While imaging, such as MRI, is useful for preoperative assessment, surgical excision remains the definitive treatment. Recurrence is uncommon but can occur. Iatrogenic seeding of endometrial cells during surgery is a likely etiological factor, highlighting the importance of proper surgical technique and wound cleaning. Cesarean scar endometriosis is often associated with a Pfannenstiel incision, with an average latency period of more than two years. Although imaging such as MRI is useful for preoperative assessment, surgical excision remains the definitive treatment. Recurrence is rare but can occur. Iatrogenic endometrial cell seeding during surgery is a likely etiologic factor, highlighting the importance of proper surgical technique and wound cleansing. The conclusion was although rare, cutaneous endometriosis should be considered in women presenting with cyclical pain and masses at surgical scars post-caesarean - cyclic pain and masses in their post-cesarean scars. Early recognition and surgical intervention are key to effective management and prevention of cutaneous endometrosis recurrence.